UP-BCO Vendor Operations Improvement Project - Antigua, Bryan Lee; Arriesgado, Jelico Angelo; Atotubo, Karol Mae.; Carasco, Roy Jensen; Caro, Ma. Christine Cecilia; Domingo, Ma. Johanna; Gonzales, Nimrod; Noveno, Kirsten Ann.; Paglinawan, Jennibeth; Punzalan, Paula Fidez (University of the Philippines Diliman, Quezon City Technology Management Center, 2012)
Assessment and improvement of food cart design in terms of Quality, Operation and Service Efficiency, and Food Safety for the Samahan ng Manininda sa UP Campus, Inc. and UP Business Concessionaires Office.
In partial fulfillment of the requirements in TM 291
Keywords: Vendor operations improvement project